2022
DOI: 10.1177/02761467221080442
|View full text |Cite
|
Sign up to set email alerts
|

PLANT VERSUS COW: Conflict Framing in the Ant/Agonistic Relegitimization of a Market

Abstract: In this article we focus on the cultural mechanisms of market evolution accompanying the marketplace discord between a market actor and a dominant industry. We situate our analysis in the intersection between marketing and institutional theory and engage specifically with the constructs of legitimacy and framing strategies, but also with Chantal Mouffe’s political philosophy concept of agonistics. To better understand the blurry impact of market-driven activism and conflict on the shaping of markets, we use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Similarly, Mikkonen et al (2011: 99) illustrate how online cadres of lifestyle activists who reject the hyper-consumerised ways of celebrating Christmas engage in mischievous anti-consumption discourses as a way of pursuing a cynical and playfully self-aware identity project, ‘the Scrooge’, rather than to genuinely educate and rescue seasonal shoppers from marketers’ manipulation. Even commercial brands sometimes seek to incite consumers’ rejection of – and resistance against – dominant market institutions, not in the pursuit of any kind of post-market politics but simply to achieve legitimacy for their own offerings (Koch and Ulver, 2022).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Similarly, Mikkonen et al (2011: 99) illustrate how online cadres of lifestyle activists who reject the hyper-consumerised ways of celebrating Christmas engage in mischievous anti-consumption discourses as a way of pursuing a cynical and playfully self-aware identity project, ‘the Scrooge’, rather than to genuinely educate and rescue seasonal shoppers from marketers’ manipulation. Even commercial brands sometimes seek to incite consumers’ rejection of – and resistance against – dominant market institutions, not in the pursuit of any kind of post-market politics but simply to achieve legitimacy for their own offerings (Koch and Ulver, 2022).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…This literature has demonstrated that the process of (de)legitimation can be facilitated by a range of actors – including producers, mainstream media, policy-makers and politicians, and consumers – and can pertain to markets (Huff, Humphreys, and Wilner 2021), brands (Giesler 2012), policies (Humphreys 2014), consumer movements or practices (Sandıkcı and Ger 2010) becoming more or less acceptable. Market actors’ work aimed at creating acceptable regulations, meanings, and understandings can enable new phenomena to attain legitimacy (Rosa et al 1999); can facilitate a shift toward legitimacy for contested phenomena (Scaraboto and Fischer 2013; Wilner and Huff 2017); and/or can facilitate a shift away from legitimacy for existing phenomena (Koch and Ulver 2022). Rather than focusing on the legitimacy of a product or market, our study focuses on the legitimacy of a specific consumer – a woman owning and using a firearm – as an institution.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Market actors can strategically use frames to achieve a desired understanding or response within a specific audience (Benford and Snow 2000). For example, prior macromarketing research showed how a plant-based milk producer used marketing messages to frame the product as wholesome and the company as sustainability-oriented, while framing conventional dairy milk as unhealthy and the producers as profit-oriented in order to shift the existing legitimacy of both categories (Koch and Ulver 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The final category of interaction involves employees working on animals as commodities, where animals serve as integrated components of the supply chain in the process of production or experimentation (Clarke & Knights, 2022;Koch & Ulver, 2022;Magri et al, 2021). The category is dominated by farmers (Ceccato, Lundqvist, Abraham, Göransson, & Svennefelt, 2022;Medaas et al, 2021), stock people (Losada-Espinosa et al, 2020), and abattoir workers (McLoughlin, 2019) but also includes scientists in research laboratories that conduct animal testing (Ferrara et al, 2022;Hobson-West, 2012;Wigham, Grist, Mullan, Wotton, & Butterworth, 2020).…”
Section: Working On Animals As Commoditiesmentioning
confidence: 99%